KEWAJIBAN PEMERINTAH MENYEDIAKAN HUNIAN TETAP (HUNTAP) BAGI KORBAN GEMPA DAN TSUNAMI DI KABUPATEN DONGGALA - Retnadumillah Saliha; Darwati Pakki (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The purpose of this paper is to analyze the Government's Obligation to Provide Permanent Shelter (Huntap) for Earthquake and Tsunami Victims in Kab. Donggalaa. By looking at the perspective of normative studies as the method used, resulting in a conclusion that, the district government. Donggalaa does not carry out its obligations as a government to be present in providing permanent housing (Huntap) for the community, especially the people in Loli Village and its surroundings. The district government should Donggalaa made the preparation of the Relocation Action Plan (RAP) Document, this document became an integral part of the Land Acquisition Plan (LAP) document and the Environmental Management and Monitoring Effort document (UKL-UPL). The Displacement Action Plan (RAP) document outlines the progress of housing readiness, profiles of disaster-affected residents, studies of relocation policies and principles, socio-economic studies and relocation action plans. Considering that the government is a manifestation of community representation in running the government system, it must be present to provide services to the needs of its people. The earthquake and tsunami that occurred in Central Sulawesi, especially in Kab. Donggalaa is a natural disaster that occurs naturally